Caregiver physical health and child maltreatment reports and rereports. (January 2020) - Chiang, Chien-Jen; Jonson-Reid, Melissa; Drake, Brett
Highlights: Self-report and official report neglect was associated with poor caregiver health. Caregiver health predicted recurrent reports among first time unserved cases. The association of caregiver health and recurrence held for young children. Neglect predicted recurrence among both served and unserved cases. Abstract: This study examined the relationship between caregiver health problems and maltreatment occurrence and recurrence, extending the limited prior research in this area. Data sources included the National Longitudinal Study of Adolescent to Adult Health and a regional longitudinal administrative data study of low income children with or without official reports of maltreatment and caregiver health diagnoses. Research questions addressed the relationship of caregiver health to child maltreatment occurrence and recurrence, with an additional emphasis on effects for younger and older children. Multinomial and Cox regression models were constructed to evaluate the research questions. Key findings included that poor caregiver health was associated with increased risk of neglect across both datasets used. In models of recurrence, caregiver health remained important, but only for families not receiving services after the initial report. Key implications of this study include the desirability of providing effective health services to families at risk for child maltreatment, and that any resultant improvements in caregiver health may result in attenuation of child maltreatment risk.